The slow failure : population decline and independent Ireland, 1922-1973 - Daly, Mary E. (History of Ireland and the Irish diaspora., 2006)
"At the outset of the twenty-first century, Ireland's population is rising, immigration outpaces emigration, most families have two or at most three children, and full-time farmers are in steady decline. But the opposite was true for more than a century, from the great famine of the 1840s until the 1960s. Between 1922 and 1966 - most of the first fifty years after independence - the population of Ireland was falling, in the 1590s as rapidly as in the 1880s. Mary E. Daly's The Slow Failure examines not just the reasons for the decline, but the responses to it by politicians, academics, journalists, churchmen, and others who publicly agonized over their nation's "slow failure." Eager to reverse population decline but fearful that economic development would undermine Irish national identity, they fashioned statistical evidence to support ultimately fruitless policies that encouraged large, rural farm families. Focusing on both Irish government and society, Daly places Ireland's population history in the mainstream history of independent Ireland. Her book is essential reading for understanding modern Irish history."--Jacket